ANALISIS NILAI EDUKATIF DALAM PANTUN ACEH - Muhamad Iqbal (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2019)
ABSTRACT This research is entitled "Educative Value Analysis in the Pantun Aceh". The details of the problems raised in it are (1) how is the moral value in educational value in the Aceh pantun, (2) how is the religious value in educational value in the Aceh pantun, and (3) how is the cultural value in educational value in the Aceh pantun. The aim is to describe the values (moral, religious, and cultural) in educative values in the Aceh pantun. The research method used is a qualitative method with a descriptive qualitative approach. The collected data is analyzed by means of document analysis. The research steps used by researchers as a research technique include: the description of the rhyme, the classification of rhyme types, and the analysis of rhymes. The results obtained from the three values (moral, religious, and cultural) studies in educational values at the Aceh pantun, are as follows: moral values in educative values talk about moral speaking, committed brushes, adab keep secrets, and noble ways; while religious values in educative values teach about the way of prayer, remembrance, and faith in Allah; and cultural values in educative values advising on matchmaking, cultural preservation, and the role of parents in their families.